Marine Vertebrate Biodiversity and Distribution Within the Central California Current Using Environmental DNA (eDNA) Metabarcoding and Ecosystem Surveys - Closek, Collin J.; Santora, Jarrod A.; Starks, Hilary A.; Schroeder, Isaac D.; Andruszkiewicz, Elizabeth A.; Sakuma, Keith M.; Bograd, Steven J.; Hazen, Elliott L.; Field, John C.; Boehm, Alexandria B. (Frontiers in Marine Science, 2019)
Environmental DNA (eDNA) metabarcoding is a new approach for assessing marine biodiversity that may overcome challenges of traditional monitoring and complement both existing surveys and biodiversity assessments. There are limited eDNA studies that evaluate vertebrate biodiversity in the marine environment or compare patterns of biodiversity with traditional methods. This study uses eDNA metabarcoding of the mitochondrial 12S rRNA genes present in seawater samples to characterize vertebrate biodiversity and distribution within National Marine Sanctuaries located in the California Current upwelling ecosystem. The epipelagic community in the study region has been monitored using traditional (mid-water trawl and marine mammal) survey methods since 1983. During 2016 and 2017, we concurrently sampled the epipelagic community using traditional survey methods and water for eDNA analysis to assess agreement among the methods. We collected replicate eDNA samples from 25 stations at depths of 10, 40, and 80 m, resulting in 131 small volume (1 L) environmental water samples to examine eDNA sequences. Across the eDNA and traditional survey methods, 80 taxa were identified. Taxa identified by eDNA partially overlapped with taxa through trawl and marine mammal surveys, but more taxa were identified by eDNA. Diversity and distribution patterns of marine vertebrates inferred from eDNA sequences reflected known spatial distribution patterns in species occurrence and community structure (e.g., cross-shelf and alongshore patterns). During both years we identified fishery taxa Sebastes (rockfish), Merluccius (hake), Citharichthys (sanddab), and Engraulis (anchovy) across the majority of the stations using eDNA metabarcoding. The marine vertebrate assemblage identified by eDNA in 2016 was statistically different from the 2017 assemblage and more marine mammals were identified in 2017 than in 2016. Differences in assemblages identified by eDNA were coincident with different oceanographic conditions (e.g., upwelling and stratification). In 2016 weak upwelling and warmer than average conditions were measured, and vertebrate assemblages were not different among ecological regions (Point Reyes, Pescadero, and Monterey Bay). While in 2017, average upwelling conditions returned, vertebrate assemblages differed at each region. This study illustrates that eDNA provides a new baseline for vertebrate assessments that can both augment traditional biomonitoring surveys and aid our understanding of changes in biodiversity.